Keluarga Beda Agama Dalam Masyarakat Jawa Perkotaan (Studi Kasus di Sinduadi Mlati Sleman Yogyakarta) - Nawari Ismail (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
This research purposes to explain the religiosity of couple both before and after marriage; to describe function of culture in the social integration among the couple which has different religion, before and after marriage; and to state the socialization of value of parent to their children. This research uses ethnographical approach in the Javanese urban, especially in Sinduadi Mlati Sleman Yogyakarta. The research is applied in some steps; exploring data, recognizing physical sphere, the research conducting, and writing report. The research revealed some point as follow: (1) Most couple have highly religious and the other are sufficient. (2) Religion, as cultural system, is very useful to integrate social factor of the couple in the religious intermarriage case that caused by values of sincreticsm of 'abangan 'subculture on the one hand, and the other hand also caused by values of secularization of 'santri' subculture, so that the tolerance attitude toward others religion is increased. (3) The role of religious culture is not dominant in socializing value and applying inheritance law.